The Effect of Unemployment on Poverty In Mandailing Natal - Siregar, Enni Sari; Batubara, Ihsan (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This study aims to analyze the effect of the unemployment rate on poverty in Mandailing Natal. This research is a quantitative research using SPSS 23 to process data. Data used is secondary data in the form of time series for the period 2001 - 2021. The results of the study conclude that the poverty equation obtained a Value t-count of 1.251 using a 95% confidence level, = 0.05 compared to the sig value obtained at 0.226, the sig value greater than α or 0.226 > 0.05. This shows that there is no significant effect between unemployment and poverty and this indicates that the poverty rate in Mandailing Natal is not determined by unemployment. If the unemployment rate increases or develops, it will not necessarily affect poverty. Furthermore, the R Square Value in this study is 0.027, indicating that the unemployment rate has an influence of 2.7 % on the poverty rate in Mandailing Natal. Furthermore , another 97.3% is influenced by other variables that were not examined in this study